KAIZEN AND LEAN IMPLEMENTATION IN PHARMACEUTICAL INDUSTRIES: A REVIEW - G, Srinivasan; N, Shah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Kaizen is one of the most commonly used words in all kind of industries. It has been implemented in organizations around the world as a way to improve production values while also improving employee morale and safety. The kaizen process brings about improvements that are small and incremental, and significant results can be seen only after a certain period of time. Many organizations across the world have adopted kaizen management philosophy and have successfully increased the efficiency of their end-to-end supply chains. With a focus on quality and regulatory compliance that are getting stringent day by day, pharmaceutical companies have been adopting these new strategies. This review focuses on basic aspects of Kaizen and Lean implementation and highlights few examples from pharmaceutical industry.